Non-Hodgkin Lymphoma of External Auditory Canal – Uncommon Location and Related Risk Factors - A D Mettias Bassem; Zeitoun Hisham (Journal of Clinical Case Reports and Images, 2018)
Objective: Presentation of rare case report of primary non-Hodgkin Lymphoma of temporal bone secondary to immunodeficiency after prolonged steroid administration in a diabetic patient. Then review the literature of similar case reports. Method: 49 years old female presented with hearing loss, facial paralysis and otalgia. Biopsy revealed high grade non Hodgkin’s B-lymphoma. She underwent chemotherapy and had remarkable response. Result: Rapidly progressive deafness, facial paralysis and otalgia are common presentations of external canal Non-Hodgkin lymphoma. The disease is common in middle age, females and has a fair response to chemotherapy, good to radiotherapy. Surgery is an alternative method in isolated lesions or recurrent cases. Conclusion: High dose steroid and type II diabetes are potential risks for acquired immunodeficiency. External Auditory canal lymphoma is uncommon sequel. Chemotherapy is very effective in treatment of isolated cases without B symptoms
Keywords: Lymphoma – External auditory canal – immunodeficiency